Intellectual Capital, Market Value, and Financial Performance: Indonesia and Malaysia’s Banking Companies - Sigit Hermawan; Nur Ravita Hanun; Nihlatul Qudus Sukma Nirwana; Clarisa Ika Candrawati (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
This study aims to determine the effect of intellectual capital on market value with financial performance as an intervening variable: evidence from banking companies in Indonesia and Malaysia. The analysis tool uses Partial Least Square to test hypotheses. The results of this study are intellectual capital affects the financial performance of banking companies in Indonesia but does not affect the banking companies in Malaysia. Intellectual capital does not affect the market value of banking companies in Indonesia but affects banks in Malaysia. Financial performance affects market value in Indonesian banking companies but does not affect banking companies in Malaysia. For indirect or mediation effects, the result is that financial performance can mediate the effect of intellectual capital on market value in banking companies in Indonesia but not for banks in Malaysia. Banking companies must pay attention to intellectual capital management because of its impact on financial performance and market value. The market will give a higher valuation to companies that have increased financial performance. Next, companies with improved financial performance will be responded positively to the market so that it will increase market value.